2013
DOI: 10.1021/jp402391n
|View full text |Cite
|
Sign up to set email alerts
|

Single Pulse Shock Tube Study of Allyl Radical Recombination

Abstract: The recombination and disproportionation of allyl radicals has been studied in a single pulse shock tube with gas chromatographic measurements at 1-10 bar, 650-1300 K, and 1.4-2 ms reaction times. 1,5-Hexadiene and allyl iodide were used as precursors. Simulation of the results using derived rate expressions from a complementary diaphragmless shock tube/laser schlieren densitometry study provided excellent agreement with precursor consumption and formation of all major stable intermediates. No significant pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 35 publications
4
33
1
Order By: Relevance
“…However, this reaction channel can be neglected as the rate constant is about two orders of magnitude lower than the 2-methylallyl radical self-recombination rate constants and does not contribute to fuel reactivity. Rate constants for this reaction are taken from Tranter and co-workers [69] for the allyl radical selfrecombination and have been divided by a factor of 2.3 to match the low temperature ignition delay time measurements, Figure 20. If the iĊ 4 H 7 radical self-recombination reaction were removed from the system, the reactivity would increase significantly in the lower temperature range as shown in Figure 21.…”
Section: Iċ 4 H 7 + Hȯ 2 ↔ Productsmentioning
confidence: 99%
“…However, this reaction channel can be neglected as the rate constant is about two orders of magnitude lower than the 2-methylallyl radical self-recombination rate constants and does not contribute to fuel reactivity. Rate constants for this reaction are taken from Tranter and co-workers [69] for the allyl radical selfrecombination and have been divided by a factor of 2.3 to match the low temperature ignition delay time measurements, Figure 20. If the iĊ 4 H 7 radical self-recombination reaction were removed from the system, the reactivity would increase significantly in the lower temperature range as shown in Figure 21.…”
Section: Iċ 4 H 7 + Hȯ 2 ↔ Productsmentioning
confidence: 99%
“…Resonantly stabilized radicals (RSRs) are typically much less reactive than other common combustion radicals such as OH, H, and O. Consequently, RSRs can accumulate in relatively large concentrations and play important roles in combustion. For instance, allyl radicals have been studied extensively ( [1][2][3] and references therein) and recently Curran et al showed the importance of allyl recombination in simulating propene ignition delay times [4,5]. The related RSR, 2-methylallyl, 2MA, plays a similarly important role in the low temperature ignition of isobutene [6] and is responsible for the effectiveness of tert-butyl ethers in suppressing engine knock [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Roth et al [9] reported rate coefficients for dissociation of 2,5-dimethyl-1,5-hexadiene (25DM15HD), the reverse of reaction 1 (Note: all reaction numbers refer to Tables 1 and S2), from single pulse shock tube (SPST) experiments over 873-1073 K and obtained k 1 from calculated thermochemical quantities and the equilibrium constant. Bayraceken et al [10] obtained k 1 at 295 K from flash photolysis of 2-methylbut-1-ene (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Torr). Tsang studied the dissociation of 2,4-dimethylhex-1-ene [11] by SPST (970-1180 K, 1-5 atm) and reported k 3 for dissociation of 2MA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous single pulse shock tube study on the recombination of allyl radicals, 48 it was shown that at the present experimental conditions allyl radicals do not readily dissociate below 1100 K, and preferentially recombined into 1,5-hexadiene. Only above 1100 K will allyl appreciably dissociation to form allene and an H atom.…”
Section: Via Methyl Nonenoate Isomer Model Developmentmentioning
confidence: 56%